Engineered Living Oriented Electrospun Fibers Regulate Stem Cell Para‐Secretion and Differentiation to Promote Spinal Cord Repair (Adv. Healthcare Mater. 9/2023). Issue 9 (5th April 2023) - Xu, Jingzhi; Xi, Kun; Tang, Jincheng; Wang, Juan; Tang, Yunkai; Wu, Liang; Xu, Yichang; Xu, Zonghan; Chen, Liang; Cui, Wenguo; Gu, Yong
Abstract : Electrospinning In article 2202785 by Liang Chen, Wenguo Cui, Yong Gu, and co‐workers, a living‐oriented fiber scaffold is found to fully exploit the advantage of stem cells, which can respond not only to regulate the local inflammatory microenvironment at the early stages of spinal cord injury, but also to further regulate the differentiation fate of stem cells, continuously release brain‐derived neurotrophic factor, and promote neuronal regeneration.